Rostellum in orchids - Kobayashi, Hideka; Arditti, Joseph (Lankesteriana: International Journal on Orchidology, 2024)
The rostellum, a small structure located above the stigma in the gynostemium of monandrous orchid flowers, separates the pollinia from the stigma, can prevent self-pollination, and plays an important role in pol- lination. It secretes a sticky exudate before and after anthesis, to which the pollinia are attached. Additionally,the viscidium, a sticky disk at the base of the stipe, also connects to the rostellum. This structure varies among species and holds taxonomic significance. For example, in Catasetum, the rostellum extends into antennae-like projections. After pollination, emasculation, or injury, the plant hormone ethylene is produced, triggering various post-pollination, post-emasculation, and post-injury processes, including changes in perianth color, senescence, and, ultimately, the death of floral segments that have completed their functions. Although the rostellum plays a significant role, it remains understudied, and many aspects of its function are still unknown. This review high- lights current knowledge and explores speculative hypotheses that may invite differing opinions and perspectives, which will likely be revised as future research deepens our understanding of its biological and ecological roles.